Perennialization and intercropping effects on cereal rhizosphere microbiome - Siwook Hwang; Joe E. Brummer; Timothy E. Crews; Lady Grant; Bridget B. McGivern; Kelly C. Wrighton; Steven J. Fonte (Applied Soil Ecology, 2026)

Correction to: A global review of white shark (Carcharodon carcharias) parturition - Craig P. O’Connell; Jon F. Dodd; Julia Crews; Juliet Gressle; Breanna Racicot; Steven Sitzer; Timothy Lis; Gregory B. Skomal (Reviews in Fish Biology and Fisheries, 2025)

Modeling carbon allocation strategies for high-yielding perennial crops - Erin Kilbane; Timothy Crews; Lee DeHaan; Michael Grillo; Brian Ohsowski; Ray Dybzinski (European Journal of Agronomy, 2025)

A global review of white shark (Carcharodon carcharias) parturition - Craig P. O’Connell; Jon F. Dodd; Julia Crews; Juliet Gressle; Breanna Racicot; Steven Sitzer; Timothy Lis; Gregory B. Skomal (Reviews in Fish Biology and Fisheries, 2024)

Perennial intermediate wheatgrass accumulates more soil organic carbon than annual winter wheat – a model assessment - Fiona H. M. Tang; Timothy E. Crews; Nathaniel A. Brunsell; Giulia Vico (Plant and Soil, 2024)
Purpose Perennial crops have been suggested as a more sustainable alternative to the currently most common cropping systems. Compared with annual plants, perennial plants produce more biomass and have deeper roots, and are expected to lead to higher soil organic carbon (SOC). This hypothesis, however, has not been well tested for grain crops. Methods Using perennial intermediate wheatgrass (IWG, Thinopyrum intermedium ) and annual winter wheat ( Triticum aestivum ) as focal species, and native grassland as reference, we quantified the SOC accumulation via a process-based model, describing water and heat exchanges and carbon-nitrogen cycling in the canopy and soil to a depth of 2 m. The model includes C fixation via photosynthesis, plant biomass growth and litter production, physical protection of SOC, depolymerisation, C mineralisation, nitrification, denitrification, microbial growth, and necromass turnover in the soil. While of general applicability, we considered a sandy loam under warm-summer humid continental climate. Results Following a conversion from native grassland, IWG reduced SOC losses by at least 38%, especially in the particulate organic carbon (POC) pool, within the top 2 m of soil, compared with annual wheat. Soil microbial biomass and soil respiration were higher in IWG than annual wheat. Shifting from annual wheat to high photosynthetic capacity IWG increased SOC by about 33 g C m −2 y −1 (averaged over a 4-year continuous IWG cropping), with a large fraction of SOC gain stemming from restoring POC. Conclusion Compared with annual grains, perennial grains can increase soil carbon sequestration and maintain SOC at levels nearer to that of native grasslands.

Discussion: Prioritize perennial grain development for sustainable food production and environmental benefits - Lee R. DeHaan; James A. Anderson; Prabin Bajgain; Andrea Basche; Douglas J. Cattani; Jared Crain; Timothy E. Crews; Christophe David; Olivier Duchene; Jessica Gutknecht; Richard C. Hayes; Fengyi Hu; et al. (Science of The Total Environment, 2023)

David Pimentel consistently promoted perennial grains as the future of agriculture - Timothy E. Crews; Siena Polk (Environment, Development and Sustainability, 2023)

Nitrate leaching losses and the fate of 15N fertilizer in perennial intermediate wheatgrass and annual wheat — A field study - Alexandra Huddell; Maria Ernfors; Timothy Crews; Giulia Vico; Duncan N.L. Menge (Science of The Total Environment, 2023)

Exploring the Role of Cryptic Nitrogen Fixers in Terrestrial Ecosystems: A Frontier in Nitrogen Cycling Research - Cory C. Cleveland; Carla R. G. Reis; Steven S. Perakis; Katherine A. Dynarski; Sarah A. Batterman; Timothy E. Crews; Maga Gei; Michael J. Gundale; Duncan N. L. Menge; Mark B. Peoples; Sasha C. Reed; Verity G. Salmon; et al. (Ecosystems, 2022)

Impact of Grazing Intensity during Drought in an Arizona Grassland - MATTHEW R. R. LOESER; THOMAS D. SISK; TIMOTHY E. CREWS (Conservation Biology, 2007)
The ecological benefits of changing cattle grazing practices in the western United States remain controversial, due in part to a lack of experimentation. In 1997 we initiated an experimental study of two rangeland alternatives, cattle removal and high‐impact grazing, and compared grassland community responses with those with more conventional, moderate grazing practices. The study was conducted in a high‐elevation, semiarid grassland near Flagstaff, Arizona (U.S.A.). We conducted annual plant surveys of modified Whittaker plots for 8 years and examined plant composition shifts among treatments and years. High‐impact grazing had strong directional effects that led to a decline in perennial forb cover and an increase in annual plants, particularly the exotic cheatgrass ( Bromus tectorum L.). A twofold increase in plant cover by exotic species followed a severe drought in the sixth year of the study, and this increase was greatest in the high‐impact grazing plots, where native cover declined by one‐half. Cattle removal resulted in little increase in native plant cover and reduced plant species richness relative to the moderate grazing control. Our results suggest that some intermediate level of cattle grazing may maintain greater levels of native plant diversity than the alternatives of cattle removal or high‐density, short‐duration grazing practices. Furthermore, episodic drought interacts with cattle grazing, leading to infrequent, but biologically important shifts in plant communities. Our results demonstrate the importance of climatic variation in determining ecological effects of grazing practices, and we recommend improving conservation efforts in arid rangelands by developing management plans that anticipate this variation.

Can the Synchrony of Nitrogen Supply and Crop Demand be Improved in Legume and Fertilizer-based Agroecosystems? A Review - Timothy E. Crews; Mark B. Peoples (Nutrient Cycling in Agroecosystems, 2005)

Changes in Asymbiotic, Heterotrophic Nitrogen Fixation on Leaf Litter of Metrosideros polymorpha with Long-Term Ecosystem Development in Hawaii - Timothy E. Crews; Heraldo Farrington; Peter M. Vitousek (Ecosystems, 2000)